Molecular Analysis of Virulent Determinants of Enterovirus 71 - Li, Renqing (Public Library of Science, 2011)
Enterovirus 71 (EV71) is the most important causative agent of hand, foot and mouth disease (HFMD) in children. In most cases, it is a self-limiting illness. However some EV71 infectious cases can develop severe clinical outcomes, such as encephalitis, meningitis, poliomyelitis like paralysis, and even death. To identify the determinants of virulence, the deduced amino acid sequence of polyprotein and nucleotide sequence of 5′-NTR and 3′-NTR in 25 SC-EV71 strains (strains from severe cases) and 31 MC-EV71 strains (strains from mild cases) were analyzed. Results showed four amino acids on two positions (Gly(P710)/Gln(P710)/Arg(P710) and Glu(P729)) on the DE and EF loop of VP1, one (Lys(P930)) on the surface of protease 2A and four nucleotides on three positions (G(P272), U(P488) and A(P700)/U(P700)) in the 5'-NTR region are associated with EV71 virulent phenotype. Predicted secondary structure of RNA using the consensus sequence of 5'-NTR by RNAStructure showed the mutation of nucleotide at position 488 in strain BJ08-Z004-3 (position 491 in prototype strain BrCr) can result in the discrepancy of an additional pair of nucleotides and thus change the stability of the second structure of IRES. Fragment base content analysis showed that in the region 696 to 714 bp at the 5'-NTR, where the A(P700)/U(P700) was located, the nucleotide constitution ratios differed significantly between SC-EV71 and MC-EV71 strains. In conclusion, comparative genomic analysis showed that virulence of EV71 strains are mainly determined by the amino acids on two positions of VP1, one position of protease 2A and the nucleotides on three positions in 5'-NTR.